Mentoring in strategic management and operational strategies for developing the dairy cooperative business of KUD Banyumanik, Semarang City - Yovita Mumpuni Hartarini; Wahyudi Wahyudi; Sopi Sopi (Universitas Muhammadiyah Magelang, 2024)
The sustainability of cooperatives will inevitably face challenges in the future. If these challenges are not anticipated and addressed properly, it will have fatal consequences for their continuity. Therefore, strategic management and operational strategy in cooperative activities are very important to consider, including for the dairy cooperative of KUD Banyumanik in Semarang City. The objective of this community service (PkM) activity is to provide assistance in strategic management and operational strategy. This PkM activity uses the Participatory Action Research (PAR) method through strategic management and operational strategy assistance activities. The evaluation results concluded that knowledge of strategic management and operational strategy increased by 80%, the ability to manage strategically and operationally increased by 75%, the ability to formulate strategic management and operational strategy increased by 84%, the skills to achieve competitive advantage through strategic management and operational strategy increased by 90%, and skills in developing and implementing strategic management and operational strategy increased by 90%.